Extracellular Matrix and Matrix Receptors in Blood-Brain Barrier Formation and Stroke - Baeten, Kim M. (2011)
The blood-brain barrier (BBB) is formed primarily to protect the brain microenvironment from the influx of plasma components, which may disturb neuronal functions. The BBB is a functional unit that consists mainly of specialized endothelial cells (ECs) lining the cerebral blood vessels, astrocytes and pericytes. The BBB is a dynamic structure that is altered in neurologic diseases, such as stroke. ECs and astrocytes secrete extracellular matrix (ECM) proteins to generate and maintain the basement membranes (BMs). ECM receptors, such as integrins and dystroglycan are also expressed at the brain microvasculature and mediate the connections between cellular and matrix components in physiology and disease. ECM proteins and receptors elicit diverse molecular signals that allow cell adaptation to environmental changes, and regulate growth and cell motility. The composition of the ECM is altered upon BBB disruption and directly affects the progression of neurologic disease. The purpose of this review is to discuss the dynamic changes of ECM composition and integrin receptor expression that control BBB functions in physiology and pathology.